If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 3) + -3x + -7 = 2 Reorder the terms: 2(3 + x) + -3x + -7 = 2 (3 * 2 + x * 2) + -3x + -7 = 2 (6 + 2x) + -3x + -7 = 2 Reorder the terms: 6 + -7 + 2x + -3x = 2 Combine like terms: 6 + -7 = -1 -1 + 2x + -3x = 2 Combine like terms: 2x + -3x = -1x -1 + -1x = 2 Solving -1 + -1x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 2 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 2 + 1 -1x = 2 + 1 Combine like terms: 2 + 1 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| x+x+x+16=25 | | 7t+6=8t | | x^2+y^2-2xy=144 | | 2a+4b+a-b+10= | | (3xy^3)-3xy=0 | | z(z-i)=iz+2 | | 7x+12=40+3x | | t/9--118=130 | | -7a+1=8(1-a)+1 | | -7b-7=-b-7 | | (2a-6)(3a-15)=0 | | -2(v-882)=162 | | z(z-i)=je+2 | | -18+35+(17)= | | -2-9r=10+2r+10 | | 20(16x+8)=12 | | 7-10n+5n=18-96 | | x^4-4x^3+4x^2-36x-45=0 | | 3f=8-5f | | 2.1x-8.9=3.9x-8.9-1.8x | | X-4y=3b | | 3(x-1)=2x-3+3 | | 8w=9+9w | | 6x^2-10x-7=0 | | (x/4)+8=-8 | | X=10x-12 | | Y^2-y+.25=0 | | 5=8m+4-7 | | 37-2x=6+7(-3x-1) | | -5+5m=-10+4m | | -4+q=-13 | | 64x^2-5=30 |